Influence of Soret effect on MHD mixed convection flow of visco-elastic fluid past a vertical surface with hall effect - Jha, Abhay Kumar; Choudhary, Kuldeep Kumar; Sharma, A. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with the unsteady motion of an MHD free convection flow of an incompressible non-Newtonian viscoelastic fluid past an infinite vertical plate in the presence of a heat source and Soret effect. A parametric study illustrating the influence of various parameters on the temperature, velocity as well as on the skin-friction and rate of heat transfer is conducted. The results of the effect of the magnetic field, the parameter describing the non-Newtonian behavior, and the velocity of suction and injection on both the velocity and temperature distributions are examined and shown graphically.
Keywords: thermal diffusion; Hall parameter; MHD; elastic parameter; Schmidt number; heat source